Pengaruh Motivasi Kerja, Gaya Kepemimpinan, dan Lingkungan Kerja Terhadap Kinerja Karyawan di Bale Ayu Resto - Cahyani, Dina Nur; Dina Nur Cahyani (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of work motivation, leadership style, and work environment on employee performance at Bale Ayu Resto. Using a quantitative approach with a survey involving 41 respondents, the results of the analysis show that work motivation and work environment have a significant positive influence on employee performance, with significance values ​​of 0.003 and 0.008, respectively. On the other hand, leadership style does not show a significant influence on employee performance, with a significance value of 0.507. Overall, the three independent variables together affect employee performance, as reflected in the F value of 6.679 and the coefficient of determination (R²) of 0.761. These results indicate that work motivation and work environment are the main factors that affect performance, while leadership style needs further attention to improve employee work results.